Petechiae and a Persistent Violaceous Nodule: A Presentation of Blastic Plasmacytoid Dendritic Cell Neoplasm to Dermatology - Madison Anzelc; Christina Druskovich; Austin Cusick; Matthew Franklin (Case Reports in Dermatological Medicine)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare, highly aggressive CD4+ CD56+ hematopoietic malignancy. The cutaneous presentation is variable but often includes violaceous nodules. We present a rare case of BPDCN, which featured dermatological findings consisting of erythematous macules, petechiae, purpura, and a violaceous nodule. A skin biopsy and peripheral blood smear supported a diagnosis of BPDCN. With BPDCN favoring cutaneous involvement, we urge dermatologists to be aware of the possibility of a BPDCN diagnosis in patients who present with purpuric nodules and petechial skin findings, especially when it is not easily explainable by another pathology or medication.